The Crippled, the Ugly and the Freak - Allué, Marta (Revista de Antropología Social, 2012)
This text is structured around a set of reflections on how society perceives the difference and how, from his look, that is constituted and constructed as a social problem that affects a few. At the same time a non-affected majority tries to solve it creating attitudes and mechanisms that far from integrate, involuntarily accent exclusion. The aim is to provide, through various ethnographic examples, a picture of the social perception on physical diversity in our close-up cultural environment.